MODEL PEMBERDAYAAN WANITA WIRAUSAHA MELALUI MOTIVATIONAL FACTORS, INTERPERSONAL SKILL FACTORS, ENTREPRENEURIAL MINDSET FACTORS - Suharyati Suharyati; Siti Hidayati; Subur Subur (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2017)
Challenges and competition in the business in Indonesia in the era of globalization is very strict at national, regional and global level. The success of entrepreneurs in Indonesia can not be separated from the role of women in efforts to develop the entrepreneurial activity. Women have contributed in improving the nation's economy through entrepreneurship. The study titled model of the empowerment of women through the Motivational Factors, Interpersonal Skill Factors, Entrepreneurial Mindset Factors, using analytical techniques such as factor analysis and the sampling technique is convenience sampling. Samples taken 100 women entrepreneurs who are members of associations of SMEs in the city of Depok. The results showed the factors that affect the motivational factors as much as 7 (seven) factors, of which there are five (5) factors that influence forming two (2) components are named with status in society, and past experiences, as well as the influence of 63.243%, Factors that affect interpersonal skills as much as nine (9) factors, of which there are four (4) factors that influence forming two (2) component named creative in problem solving and team-building skills, as well as the influence of 93.204%. Factors that affect the Entrepreneurial Mindset 8 (eight) factor, where there are four (4) factors that influence forming two (2) component named self-motivation, and risk-taking as well as the influence of 64.406%. Outcomes in this study a model of empowerment of women through the Motivational Factors, Interpersonal Skill Factors, Entrepreneurial Mindset Factors and articles to be published in national journals as well as teaching materials.